Pressure-Dependent Polymorphism and Band-Gap Tuning of Methylammonium Lead Iodide Perovskite - Jiang, Shaojie (2017)
We report the pressure-induced crystallographic transitions and optical behavior of MAPbI3 (MA=methylammonium) using in situ synchrotron X-ray diffraction and laser-excited photoluminescence spectroscopy, supported by density functional theory (DFT) calculations using the hybrid functional B3PW91 with spin-orbit coupling. The tetragonal polymorph determined at ambient pressure transforms to a ReO3-type cubic phase at 0.3 GPa. Upon continuous compression to 2.7 GPa this cubic polymorph converts into a putative orthorhombic structure. Beyond 4.7 GPa it separates into crystalline and amorphous fractions. During decompression, this phase-mixed material undergoes distinct restoration pathways depending on the peak pressure. In situ pressure photoluminescence investigation suggests a reduction in band gap with increasing pressure up to ≈0.3 GPa and then an increase in band gap up to a pressure of 2.7 GPa, in excellent agreement with our DFT calculation prediction. This work lays the foundation for understanding the pressure-dependent phase transition of MAPbI3 and potentially enriches the toolkit for engineering perovskite polymorphs with exceptional optical properties.